Comparing the Rate of Nicotine Metabolism Among Smokers With Current or Past Major Depressive Disorder. Issue 4 (26th March 2021) - Schnoll, Robert; Paul Wileyto, E.; Bauer, Anna‐Marika; Fox, Erica; Leone, Frank; Lerman, Caryn; Tyndale, Rachel F.; George, Tony P.; Hawk, Larry; Cinciripini, Paul; Quinn, Mackenzie; Purnell, Janelle; et al.
Abstract : Background and Objectives: Persons with current or past major depressive disorder (MDD) vs those without have higher smoking rates. The nicotine metabolite ratio (NMR) represents variation in the rate of nicotine metabolism and has been associated with smoking behaviors and response to tobacco treatments. We compared NMR between smokers with current or past MDD (MDD+) vs smokers without MDD (MDD−). We also assessed correlates of NMR and compared withdrawal and craving between MDD+ and MDD− smokers. Methods: Using baseline data from two clinical trials and propensity score weighting based on sex, race, body mass index, and smoking rate, we compared NMR between MDD+ ( N  = 279) and MDD− ( N  = 1575) smokers. We also compared groups on and nicotine withdrawal and craving. Results: Mean NMR ( β  = −.02, 95% confidence interval [CI]: −0.05 to 0.01, P  = .13) and the distribution of smokers across NMR quartiles (odds ratio [OR] = 0.76, 95% CI: 0.50 to 1.16, P  = .21) were similar between MDD+ and MDD− samples. This relationship was not affected by antidepressant medication. In the MDD+ sample, African Americans had significantly lower mean NMR, while older smokers and smokers with lower education had higher mean NMR ( P s < .05). MDD+ smokers had significantly higher withdrawal and craving than MDD− smokers ( P s < .05). Discussion and Conclusions: While variability in NMR may not explain differences in smoking rates between MDD+ and MDD− smokers, MDD+ smokers report increased withdrawal and craving. Scientific Significance: In this first study to assess NMR among MDD+ smokers, the findings underscore the need to address withdrawal and craving within smoking cessation treatments for those with MDD. (Am J Addict 2021;00:00–00)